Test of Breadfruit Leaf Extract Cream Preparation (Artocarpus Altilis) and Antioxidant Activity Test with DPPH Method - Nirwana Sembiring; Ali Napiah Nasution; Muhammad Faridz Syahrian; Zulfikri Mukhtar; Lenni Dianna Putri; Antje Irmella Tarigan; Ermi Girsang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The skin, which accounts for approximately 15% of body weight, is the body's outermost organ and serves as a barrier between the body and the environment. Skin color varies, ranging from fair to dark, with different shades on various parts of the body. Protecting the skin from inflammation, cancer, and premature aging caused by free radicals is crucial, and skin care cosmetic preparations are essential for achieving this goal (Wahyuni, 2005). This research aimed to investigate the antioxidant activity of breadfruit leaf extract and assess its suitability for use in cream preparations. This experimental laboratory study evaluated the potential of breadfruit leaf extract cream as an antioxidant agent. The experimental method involves manipulating the research object and using controls to investigate the cause-and-effect relationship between treatments and their effects (Sugiyono, 2014). Phytochemical screening of breadfruit leaf simplisia powder showed the presence of flavonoids, alkaloids, saponins, tannins, triterpenoids/steroids and glycosides. The content water of the simplisia was 7.30%, while the water-soluble juice and ethanol-soluble juice contents were 26.70% and 15.14%, respectively. The total ash content was 9.99%, and the ash content was 5.06%. Breadfruit leaf essence exhibited strong antioxidant activity, with an IC50 score of 28.10 ± 0.15 compared to quercetin, which also demonstrated strong antioxidant activity with an IC50 score of 9.76 ± 0.07 μg/mL. Breadfruit leaf extract has potent antioxidant activity, and its cream preparations meet the necessary requirements